Religious and Cash Holding: Evidence from Indonesia - Hendrawaty, Ernie; Pranyoto, Edi; Abubakar, PhD, Adam Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research examines the effect of religiosity on the cash holding. The method used to test the model is panel data regression by investigating the effect of religiosity on the cash holding of shari'a and non-shari'a companies. The results show that Religiosity (Islamic Dichotomic), showing a positive and significant coefficient on cash holdings. Companies with a high level of religiosity hold significant amounts of cash. The companies hold cash to reduce risk by reducing debt financing. Keywords: cash holdings, religiosity, risk